Simulation Of A Design Environment For Users To Incorporate Proportioning Systems Into Screen Design - Eugene, Ch'ng (2002)
Dynamic Symmetry has been around for a long time. But rarely do we hear any discussion about its use as a design tool. "(It) is now all butt forgotten, but in its day, it produced a cult-like mass of followers in the art schools." Dynamic symmetry was discovered by Jay Hambidge in the early 1920s and used as a means for art, design and architecture as an objective method of aesthetics design. The base of this proportioning system originated from the natural growth patterns of organisms. One of the very distinct properties of this system is the theme principles of this system yield very orderly and natural relationships betwen elements and the elements and the whole.